UTOPIANISM IN WILDE'S THE HAPPY PRINCE - Marsela Fledisti Potu; Fivy A. Andries; Imelda Lolowang (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The purpose of this study is to discuss the utopianism that exists in short story The happy prince by Oscar Wilde. The researcher uses qualitative methods because the data to be collected is based on words not based on numerical calculations. According of Sugiono (2005) which means that qualitative research is more suitable for this type of research that understands social phenomena from the participant's perspective. In simple terms, it can also be interpreted as research that is more suitable to be used to examine the conditions or situations on the object of research. The author tries to describe the ideals of society in short story the happy prince and this research used a descriptive analysis, which is an analysis that aims to describe the existing phenomena. The character of the happy prince who creates social conditions where the social utopianism that the prince seeks and wants to form is willing to give all the gems and gold in his body to realize the welfare of the people in his city. Oscar Wilde not only describes what utopian is but also gives an idea of ​​how utopian is realized. The welfare of the whole community in one city that is cultivated and realized by a prince, and also creates an ideal place, buildings and beautiful city arrangements. By using a sociological approach in analysing existing data, it can be concluded that the short story written by Oscar Wilde, especially the happy prince, describes utopianism